Group Works on Open Source Interoperability. - Paulson, Linda Dailey (Computer (00189162), 2007)
The article discusses how a consortium of software developers is working to ensure compatibility of open source software from different vendors. The consortium, the Open Solutions Alliance (OSA), hopes to compete with large software companies by establishing guidelines for interoperable programs and increasing cooperation between software developers. The OSA may recommend application programming interfaces (API) to ensure programs are compatible. The OSA is developing an interoperability prototype called the Common Customer View (CCV) to allow users to log onto multiple applications simultaneously. Barry Klawans, chief technology officer (CTO) at software vendor Jaspersoft, comments that the OSA will serve as a resource for companies.